Noise-enhanced encryption for physical layer security in an OFDM radio - Reilly, D.; Kanter, G.S. (2009 IEEE Radio and Wireless Symposium, 2009)
We adapt a physical-layer modulation scheme previously used for enhancing security in the optical domain to an OFDM radio link. The method relies on manipulating the signal constellation according to a cryptographic pseudo-random number generator and adding a small amount of truly random noise at the transmitter. We test the ultra-secure format by generating modified 802.11a packets offline and transmitting them over-the-air using a radio board designed for software defined radio applications. Our initial test system uses an underlying QPSK data format with a 12Mb/s burst-mode data rate. No performance penalty was observed by adding the noise-enhanced encryption function.